2020
DOI: 10.3390/jcm9041062
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Strategies in Patients with Atrial Fibrillation Following Percutaneous Coronary Intervention: A Systemic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: Up to 10% of patients with atrial fibrillation (AF) undergo percutaneous coronary intervention (PCI). A systematic review and network meta-analysis were conducted by searching PubMed, Embase, and the Cochrane database of systematic reviews for randomized control trials that studied the safety and efficacy of different antithrombotic strategies in these patients. Six studies, including 12,158 patients were included. Compared to that in the triple antithrombotic therapy group (vitamin K antagonist (VKA) plus P2Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although some differences among studies exist especially given the different included trials and selected outcomes, overall evidence demonstrates that dual therapy with an DOAC and P2Y12 inhibitor is superior to triple therapy. 10 The gradual introduction over the past decade of the DOACs to be used in different cardiovascular conditions aimed for a more convenient and fixed-dose regimen compared to previous therapies. New oral anticoagulants have many theoretical advantages over warfarin, including comparable or superior efficacy in trial populations (eg, in AF, reduced risk of stroke, thromboembolism, an all-cause mortality) and reduced monitoring requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some differences among studies exist especially given the different included trials and selected outcomes, overall evidence demonstrates that dual therapy with an DOAC and P2Y12 inhibitor is superior to triple therapy. 10 The gradual introduction over the past decade of the DOACs to be used in different cardiovascular conditions aimed for a more convenient and fixed-dose regimen compared to previous therapies. New oral anticoagulants have many theoretical advantages over warfarin, including comparable or superior efficacy in trial populations (eg, in AF, reduced risk of stroke, thromboembolism, an all-cause mortality) and reduced monitoring requirements.…”
Section: Discussionmentioning
confidence: 99%
“…New oral anticoagulants have many theoretical advantages over warfarin, including comparable or superior efficacy in trial populations (eg, in AF, reduced risk of stroke, thromboembolism, an all-cause mortality) and reduced monitoring requirements. [38][39][40][41][42] Five main RCTs comparing the use of different regimens of DOAC plus P2Y12 inhibitor in patients with AF undergoing PCI have been performed, and were included in both NMAs published by Lopes et al and Chua et al [10][11][12] Additionally, Chua et al included the ISAR-TRILPE trial (2015) 43 which evaluates whether shortening the duration of clopidogrel therapy (from 6 months to 6 weeks) after stent implantation was associated with a superior clinical outcome in patients receiving concomitant aspirin and OAC. The results of this trial demonstrated no significant differences on the duration of triple therapy with respect to net clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral anticoagulant therapies (OAC), which are broadly classified into vitamin K antagonists (VKA) and direct oral anticoagulants (DOAC), are highly effective for the management of thromboembolic disorders; their use reduces the risk of stroke and systemic embolism by around two thirds [ 5 , 6 ] . However, these therapies are considered high-risk medications.…”
Section: Introductionmentioning
confidence: 99%